Forage quality on family farms in Croatia: hay quality monitoring over the two winter feeding seasons of dairy cows - Marina Vranić; Mladen Knežević; Josip Leto; Goran Perčulija; Krešimir Bošnjak; Hrvoje Kutnjak; Luna Maslov (Mljekarstvo)
The aim of the applied research project:“Forage evaluation by NIR spectroscopy” was to monitor the nutritive value of grass silage, corn silage and hay on family farms in Croatia over 6-month feeding in each of the two investigation years (from November 2003 to May 2004 and from November 2004 to May 2005). In this paper the nutritive value of hay on 18 dairy farms over the second year of investigation and the comparison of the results with the first year was done. Extension service staff recommended dairy nutrition based on monthly silage analysis by NIRS instrument (Foss, Model 6500).The following parameters were estimated: dry matter (DM), crude protein (CP), neutral detergent fiber (NDF), metabolizable energy (ME), water-soluble carbohydrates (WSC) and organic matter digestibility in DM (D-value). The average results show desirable DM content (873.30 g kg-1), high NDF (671.16 g kg-1DM), but low WSC (83.53 g kg-1 DM), CP (61.75 g kg-1 DM), ME (8.75 MJ kg-1 DM) and D-value (58.33%). Great variations were observed for CP (40-133 g kg-1 DM), ME (6-11.7 MJ kg-1DM), WSC (21-160 g kg-1 DM) and D-value (40-78%). Statistically significant differences (P<0.05) among family farms were recorded for CP (P<0.05) that varied from 40-112.4 g kg-1 DM. No statistically significant differences were observed in the investigated parameters between the first and the second year of the investigation.